Three new species of the genus Nemophora Hoffmannsegg (Lepidoptera, Adelidae) from Southeast Asia - Kozlov, Mikhail V. (Zootaxa, 2020)
Three new, beautifully patterned species of the genus Nemophora Hoffmannsegg are described from Myanmar (N. alba sp. nov.), Indonesia (N. decoratella sp. nov.) and Borneo (N. bruneiella sp. nov.). Nemophora alba differs from all known Nemophora species by white colour of the body, including head, thorax, abdomen, legs, and larger part of wings. Nemophora bruneiella and N. decoratella share two possible synapomorphies, which distinguish them from other Nemophora species: forewing with four to five compact small dark brown spots along dorsum, and basal field of forewing with silver-white triangular spot adjacent to internal border of fascia. The taxonomic affinities of the described species with the other members of the genus Nemophora remain unknown.